Muqaddimah of Idea: The Reflection from the New Perspective - Ab Gani, Muhammad Abdul Aziz; Ramli, Ishak (Idealogy Journal, 2022)
We would like to present, with great pleasure, the seventh volume of a scholarly journal of arts and social science. This journal is devoted to the gamut of arts and social science issues, from theoretical aspects to application-dependent studies and the validation of emerging technologies in arts. This journal was envisioned and founded to represent the growing needs of arts and social science as an emerging and increasingly vital field. Its mission is to become a voice of the arts and social science community, addressing researchers and practitioners in areas ranging from arts to applied arts, from design to technology in design, from humanity to social science, presenting verifiable arts methods, findings, and solutions. Transactions on arts focuses on original high-quality research in the realm of social science in parallel and distributed environments, encompassing facilitation of the theoretical foundations and the applications of arts to massive daily life. The Journal is intended as a forum for practitioners and researchers to share arts techniques and solutions in the area, to identify new issues and to shape future directions for research. In this issue, most of the articles are discussing on the topic of arts and the social science. In social science it is very important to have a combination of different discipline to ensure the survival of knowledge. By combining knowledge from different fields, it could produce new innovation that could lead to solutions to many important problems or issues. Hence, Idealogy Journal is a platform for many fields of knowledge to share research findings as well as literatures. Associate Professor Dr Muhamad Abdul Aziz Ab Gani Ishak Ramli Chief Editors Ideology Journal idealogyjournal@gmail.com